2016
DOI: 10.1007/s13197-016-2254-4
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy for rapid classification of fruit spirits

Abstract: Multivariate analysis combined with near-infrared (NIR) spectral analysis was evaluated to classify fruit spirits. A total of 67 fruit spirits (12 apple, 18 apricot, 19 pear and 18 plum spirits) were analyzed. NIR spectra were collected in the wavenumber range of 4000-10,000 cm(-1). Linear discriminant analysis based on principal component analysis (PCA-LDA) and general discriminant analysis (GDA) based directly on NIR spectral data were used to classify the samples. The prediction performance of models in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…Figure 4 exhibits a representative NIR spectrum of the AWS, similar to those obtained by other authors for wine spirit, grape marc spirit, fruit spirits, whisky and vodka [ 28 , 29 , 37 , 40 , 41 , 42 , 43 ].…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Figure 4 exhibits a representative NIR spectrum of the AWS, similar to those obtained by other authors for wine spirit, grape marc spirit, fruit spirits, whisky and vodka [ 28 , 29 , 37 , 40 , 41 , 42 , 43 ].…”
Section: Resultssupporting
confidence: 68%
“…Regarding Figure 3 , it is possible to establish that the NIR spectra followed the trend of sample differentiation, which was also observed in Figure 2 . However, NIR spectra showed that other compounds present in AWS could affect their relative position along the PCA axes [ 8 , 39 , 40 ]. In Figure 3 , the AWS samples aged with chestnut wood and Limousin oak wood are presented separately to understand better.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance data from the preprocessed NIR spectrum were then analyzed using XLSTAT version 2019. 4…”
Section: Chemometrics Analysismentioning
confidence: 99%
“…12 Jakubikova et al classified 67 fruit spirits (apple, apricot, pear and plum spirits) by type using NIR combined with multivariate analysis. 13 Although there are numerous reports on the use of NIR spectroscopy in food and beverage analysis, 9,10,[12][13][14][15] the potential of NIR spectroscopy in the wine spirit/brandy ageing degree estimation have not been studied.…”
Section: Introductionmentioning
confidence: 99%